AVALIAÇÃO DE MÉIS COM INDICAÇÃO MONOFLORAL, COMERCIALIZADOS NA REGIÃO DOS CAMPOS GERAIS – PR - Borsato, Débora Maria (2008)
Honey is a very traditional food. In additional, several customers have been daily used a large number of honeys due to their particular nutritional quality (e.g. vitamins and minerals), high energy values, their medicinal uses (as antioxidant and antiseptic properties) and their sensorial features. Moreover some aspects of the commercially available honeys as price and quality are usually related to their botanical origin or chemical compositions. The aim of this work was to perform the botanical authentication and to investigate the antioxidant and antimicrobial activities of samples (n=13) labeled as monofloral honeys from the region of Campos Gerais, Paraná, Brazil. Eight samples analyzed was according to the Brazilian regulation and five achieved low values for the required diastase index. The botanical origin was reported by the pollen analysis. Six samples were regarded as monofloral honeys. The other honey samples were of bifloral (n=1) or heterofloral (n=6) origin. All analyzed honeys presented total phenolic in mg EC.100g-1 of honey, varying between 30,40 (± 0,74) and 176,07 (± 2,53). The antioxidant activity in phenolic extract (10) varied between 31,66 (± 1,11) and 75,23 (± 0,76), with a correlation of 0.7021 between these parameters. When sensibility of the microorganisms (Staphylococcus aureus and Escherichia coli) and antimicrobial activity were studied, an unrelated behavior was verified.